Fjellrev i Finnmark : forskning og tiltak 2006 - Knutsen, Kjartan; Ims, Rolf Anker; Killengreen, Siw Turid; Mørk, T.; Langeland, K.; Yoccoz, Nigel Gilles; Henden, John-André; Ravolainen, Virve (Universitetet i Tromsø, 2006)
Faglig årsrapport for 2006 til DN.